Review of the 'fault' principle in divorce proceedings under the Law Reform (Marriage and Divorce) Act 1976 / Dr Nuraisyah Chua Abdullah - Chua Abdullah, Dr Nuraisyah (Research Management Institute (RMI), 2011)
The application of fault principle in divorce proceedings under the LRA is problematic and this is made worse when the domicile issue is raised. In the absence of detailed discussion on the issue of fault principle and domicile in Malaysia, this research aims to examine the rationale, advantages and disadvantages of the current fault principle in Malaysia and explores the possibility of adopting the no fault principle into the Law Reform (Marriage and Divorce) Act 1976. Library based research is adopted where comparative study with the position in UK, various states in US, Canada, Australia and Singapore are made and interviews with the various officers of the Marriage Tribunals are conducted in this research. It is also suggested that if the LRA is to apply no-fault divorce law, it is strongly recommended that Malaysia should retain the application of domicile. However, it is suggested that the wives under the LRA has the right to acquire her own domicile and need not depend on the husband's domicile and that a specific provision is provided to such effect. In the absence of provision in the LRA regarding the status of foreign divorce judgement, it is recommended that an addition to the provision on foreign divorce judgment is made in the LRA and that the Hague Convention for the Recognition of Divorces and Legal Separations is seriously to be considered. The research suggests the repeal or amendment of section 47 of the LRA where this would be the first step in enabling section 51 to be amended to include the right of convert spouse to petition for divorce. The amendment of section 47 also would then settle the dispute of whether there is need to proof breakdown of marriage in petition for divorce under mutual consent (section 52). By repealing section 47 of the LRA, judges would no longer be obliged to follow the approach of English judges which would appear to contradict the express provisions of section 54(1 )(b) and (d). It is also suggested that repeal of section 53 which clearly provides breakdown of marriage as the sole ground of divorce; should be highly considered and this repeal will go in line with the repeal of section 47 of the LRA. Hence, if the LRA continues to adopt the mixed fault and no-fault system that is currently applied right now, then it is viewed that section 54 can also be maintained and is suggested that more ‘no fault' grounds are being adopted under the LRA for example irreconcilable differences and incompatibility.